Dietary advanced glycation endproducts (AGEs) increase their concentration in plasma and tissues, result in inflammation and modulate gut microbial composition in mice; evidence for reversibility. (September 2021) - van Dongen, Katja C.W.; Linkens, Armand M.A.; Wetzels, Suzan M.W.; Wouters, Kristiaan; Vanmierlo, Tim; van de Waarenburg, Marjo P.H.; Scheijen, Jean L.J.M.; de Vos, Willem M.; Belzer, Clara; Schalkwijk, Casper G.
Graphical abstract: In this study, we found accumulation of advanced glycation endproducts (AGEs) in liver, kidney and plasma in mice after a 10-week baked chow diet high in AGEs compared to a standard chow diet low in AGEs. In addition, gut microbiome composition, assessed by 16S rRNA analysis, differed significantly between groups and markers of inflammation were increased. Remarkably, by including a switch diet group fed 5 weeks the baked chow high AGE diet and 5 subsequent weeks of standard chow low AGE diet, we found that these effects were reversible or discontinued. Highlights: Advanced glycation endproducts (AGEs) are formed in food exposed to heat. A baked chow high-AGE diet led to an increase of AGEs in plasma and organs, and inflammatory markers in mice. Gut microbial composition was altered after a baked chow high-AGE diet. An increase in AGEs and inflammation and a change in microbial composition were reversible by switching to a low-AGE diet. This reversibility has implications for reducing AGE-associated biological effects. Abstract: Scope: Dietary advanced glycation endproducts (AGEs) are associated with negative biological effects, possibly due to accumulation in plasma and tissues and through modulation of inflammation and gut microbiota. Whether these biological consequences are reversible by limiting dietary AGE intake is unknown. Methods and results: Young healthy C57BL/6 mice were fed a standard chow (n = 10) or a baked chow high AGE-diet (n = 10) (~1.8–6.9 fold increased protein-bound Nε-(carboxymethyl)lysine (CML), Nε-(1-carboxyethyl)lysine (CEL), and Nδ-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1)) for 10 weeks or a switch diet with baked chow for 5 weeks followed by 5 weeks of standard chow (n = 10). We assessed accumulation of AGEs in plasma, kidney, and liver and measured inflammatory markers and gut microbial composition. After 10 weeks of baked chow, a substantial panel of AGEs were increased in plasma, liver, and kidney. These increases were normalized after the switch diet. The inflammatory z-score increased after the baked chow diet. Gut microbial composition differed significantly between groups, with enriched Dubosiella spp. dominating these alterations. Conclusion: A high AGE-diet led to an increase of AGEs in plasma, kidney, and liver and to more inflammation and modification of the gut microbiota. These effects were reversed or discontinued by a diet lower in AGEs.